Evektifitas Pembelajaran Matematika dengan Model Pembelajaran Problem Based Learning Berbasis Powerpoint terhadap Kemampuan Pemahaman Konsep Matematika SMP N 4 Pekalongan pada Materi Statistika - Lia Candra Utami Lia; Dewi Mardhiyana (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2023)
This study aims to determine the ability to understand concepts with problem-based learning models better than direct learning models in class VIII statistics material at SMP N 4 Pekalongan and to determine students' conceptual understanding abilities to achieve completeness by applying problem-based learning models based on powerpoint learning statistical materials class VIII SMP N 4 Pekalongan. This research includes quantitative research in the form of an experimental study with a Quasi Experimental Design. Data was collected using a test technique. The respondents in this study were 32 class VIII students at SMP Negeri 4 Pekalongan in the 2022/2023 academic year. Preliminary data analysis includes normality test and homogeneity test. The average similarity test is used to determine the average similarity between the experimental class and the control class. Final data analysis in this study consisted of hypothesis 1 test (mean difference) and hypothesis 2 test (proportion test). The results of this study indicate that the ability to understand mathematical concepts of students who are taught using the Powerpoint-based Problem Based Learning learning model is better than the ability to understand mathematical concepts of students who are taught using the direct learning model and the ability to understand the concepts of students who are taught using the Powerpoint-based Problem Based Learning model. has achieved completeness by getting a score of â‰¥ 70 more than 75%.